2012
DOI: 10.1007/s10585-012-9494-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGFβ3 and its effects on migratory and invasive behavior of prostate cancer cells: involvement of PI3-kinase/AKT signaling pathway

Abstract: Transforming growth factor-β (TGFβ) is a secreted cytokine implicated as a factor in cancer cell migration and invasion. Previous studies have indicated that TGFβ isoforms may exert differential effects on cancer cells during different stages of the disease, however very little is known about the expression patterns and activity of the three isoforms in prostate cancer. Non-traditional signaling pathways including the PI3-Kinase have been associated with TGFβ-mediated effects on cancer cell invasion. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…All cells were cultured in the recommended growth media at 37°C with 5% CO 2 and 100% humidity as described previously (29,64).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All cells were cultured in the recommended growth media at 37°C with 5% CO 2 and 100% humidity as described previously (29,64).…”
Section: Methodsmentioning
confidence: 99%
“…4 l of the diluted cDNA were added to separate RT-PCR mixtures following established procedures. All gene-specific primers were designed with Beacon-Designer version 5.0 as described previously (29). The following primers were used: c-Jun forward, 5Ј-TGGAAACG-ACCTTCTATGACGA-3Ј; c-Jun reverse, 5Ј-GTTGCT-GGACTGGATTATCAGG-3Ј; JunB forward, 5Ј-TACCACG-ACGACTCATACACA-3Ј; JunB reverse, 5Ј-CGCTTTGAGA-CTCCGGTAGG-3Ј; JunD forward, 5Ј-CAAACCCTGCCTT-TCCTTTAC-3Ј; JunD reverse, 5Ј-GGCGAACCAAGGAT-TACAAA-3Ј; L19 forward, 5Ј-GAAATCGCCAATGCCAA-CTC-3Ј; L19 reverse 5Ј-TCTTAGACCTGCGAGCCTCA-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LY294002 can also inhibit fibroblast growth factor 2-stimulated migration of the periodontal ligament cells through suppressing Akt activation (32). Recently, Walker et al (47) reported that transforming growth factor ␤3 significantly induced motility of human prostate cancer PC3 cells by increasing the level of phosphorylated Akt (Ser 473), and LY294002 blocked transforming growth factor ␤3-stimulated migration via the suppression of Akt phosphorylation at Ser 473. These studies revealed that Akt phosphorylation is closely associated with cell migration, supporting our hypothesis that C. pneumoniae infection promotes VSMC migration possibly by inducing Akt phosphorylation.…”
Section: Figmentioning
confidence: 99%